Fatty acid wax from epoxidation and hydrolysis treatments of waste cooking oil: synthesis and properties. Issue 55 (15th December 2022) - Liu, Yan; Fan, Xin-Gang; Liu, Meng-Yu; Wang, Lei; Wang, Peng-Yu; Xu, Han-Rui; Chen, Yu-Xin; Chen, Shuo-Ping
Abstract : A fatty acid wax based on waste cooking oil was synthesized and could be a lower-cost alternative of commercial soybean wax. Abstract : To provide low-cost wax and a new methodology for utilizing waste cooking oil (WCO), fatty acid wax based on WCO was synthesized by using epoxidation and hydrolysis treatments, whose properties included melting point, color, hardness, combustion properties, aldehyde content, and microscopic morphology were tested and analyzed. The obtained WCO-based wax contained mixed fatty acids, including palmitic acid and 9, 10-dihydroxystearic acid as main constituents, which could form a 3D stable crossing network constructed by large long-rod crystals. The WCO-based wax with high fatty acid content (96.41 wt%) has a high melting point (44–53 °C), light color (Lovibond color code Y = 11.9, R = 2.3), good hardness (needle penetration index = 2.66 mm), long candle burning time (293 min), and low aldehyde content (7.98 × 10 −2 μg g −1 ), which could be a lower-cost alternative of commercial soybean wax (SW) for producing various wax products including candles, crayons, waxworks, etc.